PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN PEMBELAJARAN IPS TENTANG MASALAH SOSIAL UNTUK SISWA KELAS IV SDN 1 PEJAGOAN TAHUN AJARAN 2014/2015 - Lusnanto, Sigit (KALAM CENDEKIA PGSD KEBUMEN, 2015)
ABSTRAKSigit Lusnanto. PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN PEMBELAJARAN IPS TENTANG MASALAH SOSIAL UNTUK SISWA KELAS IV SDN 1 PEJAGOAN TAHUN AJARAN 2014/2015. Skripsi, Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta. Mei 2015.Tujuan penelitian ini adalah (1) mendeskripsikan langkah-langkah penerapan model Problem Based Learning untuk meningkatkan pembelajaran IPS tentang masalah sosial untuk siswa kelas IV SDN 1 Pejagoan, (2) mendeskripsikan peningkatan pembelajaran IPS tentang masalah sosial melalui penerapan model Problem Based Learning untuk siswa kelas IV SDN 1 Pejagoan, dan (3) mendeskripsikan kendala dan solusi penerapan model Problem Based Learning untuk meningkatkan pembelajaran IPS tentang masalah sosial untuk siswa kelas IV SDN 1 Pejagoan.Penelitian ini merupakan penelitian tindakan kelas (PTK). Penelitian dilaksanakan dalam tiga siklus, dengan tiap siklus terdiri atas perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas IV SDN 1 Pejagoan yang berjumlah 32 siswa. Data berasal dari siswa, teman sejawat, guru kelas IV, dan dokumen. Teknik pengumpulan data adalah dengan tes hasil belajar, wawancara, observasi, dan dokumen. Validitas data menggunakan teknik triangulasi sumber dan triangulasi teknik. Analisis data menggunakan teknik analisis data kuantitatif dan analisis data kualitatif, meliputi reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi.Hasil penelitian menunjukkan bahwa (1) Langkah model Problem Based Learning yang dapat meningkatkan hasil belajar IPS tentang masalah sosial kelas IV SDN 1 Pejagoan yang tepat yaitu: (a) orientasi masalah, (b) pengorganisasian belajar, (c) pembimbingan individual maupun kelompok, (d) penyajian hasil kerja atau diskusi, dan (e) analisis dan evaluasi proses pemecahan masalah; (2) Adanya peningkatan hasil belajar IPS tentang masalah sosial siswa kelas IV SDN 1 Pejagoan. Pada siklus I jumlah siswa yang tuntas adalah 60,93%, Siklus II menjadi 76,56%, dan siklus III menjadi 90,62%; dan (3) Kendala yang ditemui pada penggunaan model Pembelajaran Berbasis Masalah yaitu: (a) guru kurang menertibkan siswa, (b) guru kurang memotivasi siswa, (c) guru kurang aktif memandu siswa, (d) siswa kurang aktif dalam diskusi, (e) siswa kurang aktif dalam tanya jawab, dan (f) siswa tidak memperhatikan penjelasan guru. Solusi untuk mengatasi kendala tersebut (a) guru lebih menertibkan siswa, (b) guru memotivasi belajar siswa, (c) guru lebih aktif memandu kerja sama siswa, (d) guru membagi tugas diskusi kelompok, (e) guru memancing siswa untuk mengungkapkan pendapat, dan (f) guru melibatkan siswa dalam pembahasan materi. Kata kunci: Problem Based Learning, IPS, masalah sosial  ABSTRACTSigit Lusnanto. THE APPLICATION OF PROBLEM BASED LEARNING IN IMPROVING SOCIAL SCIENCE LEARNING ABOUT SOCIAL PROBLEM FOR THE FOURTH GRADE STUDENTS OF SDN 1 PEJAGOAN IN THE ACADEMIC YEAR OF 2014/2015. Thesis, Teacher Training and Education Faculty, Sebelas Maret University of Surakarta. May 2015.The objectives for this research are (1) to describe the steps of the application of Problem Based Learning model to improve social science learning about social problem for the fourth grade students of SDN 1 Pejagoan, (2) to describe the improvement of social science learning about social problem by using Problem Based Learning model for the fourth grade students of SDN 1 Pejagoan, and (3) to describe problems and solutions in the application of Problem Based Learning model in improving social science learning about social problem for the fourth grade students of SDN 1 Pejagoan.This research is collaborative Classroom Action Research (CAR). This research implemented within three cycles and each cycle consisted of planning, action, observation, and reflection. Subjects of this research were 32 students in the fourth grade of SDN 1 Pejagoan. Sources of data were derived from students, classmates, teachers, and documents. Techniques of collecting data were test, interview, observation, and document. Validity of data used triangulation of technique and sources. Data were analyzed using qualitative and quantitative data, namely data reduction, data display, and drawing conclusion or verification.The results of this research show that (1) the steps of Problem Based Learning model can improve social science learning outcomes about social problem for the fourth grade students of SDN 1 Pejagoan if implemented by appropriate steps, namely: (a) problem orientation, (b) study organization, (c) guidance in individual or team, (d) presenting result or discussion, and (e) analyzing and evaluating of problem solving process; (2) the application of Problem Based Learning model can improve social science learning outcomes for the fourth grade students of SDN 1 Pejagoan. It was proved by the increase of learning outcomes in each cycles. Passing grade percentage of students result in the first cycle was 60.93%, in the second cycle was 75.56%, and in the third cycles was 90.62%; and (3) the problems found in the application of Problem Based Learning model, namely: (a) the teacher did not ask the students to be discipline, (b) the teacher lack in motivating the students, (c) the teacher did not lead students, (d) the students were passive in discussion, (e) the students were passive in question and answer, and (f) the students did not concern in teacher?s explanation. Solutions to solve these problems, namely: (a) the teacher ask the students to be discipline, (b) the teacher have to motivate the students to study, (c) the teacher should be more active in leading students? team work, (d) the teacher provides tasks for team discussion, (e) the teacher asks students to reveal their opinion, and (f) the teacher involves students in material discussion.  Keywords: Problem Based Learning, social science, social problem